Obstacles of using virtual science laboratories in the scientific faculties of Ubari region, as perceived by faculties members and their assistants. (Sebha University Conference Proceedings, 2025)
This study sought to identify impediments to the utilization of virtual science laboratories in Ubari's scientific faculties from faculties members and their assistant perspectives, while assessing statistical significance at the (0.05 ≥α) level regarding these impediments across variables such as gender, academic degree, and experience. To fulfill this objective, a descriptive analytical methodology was employed, utilizing a 27-statement questionnaire categorized into four domains, with a sample of 31 faculty members from three Ubari scientific faculties (Faculty of Arts and Sciences, Ubari, Faculty of Education, Al-Gharifa, Faculty of Medical Technology and Rehabilitation, Ubari). The analysis data was performed by using various statistical methods including standard deviation, arithmetic means, T-tests, and ANOVA. Findings indicated that the obstacles limiting virtual science lab usage in Ubari's scientific faculties were classified as "High" with the primary impediments ranked as follows:1. obstacles related to educational structure, 2. obstacles related to virtual software, 3. obstacles related to faculty members, 4. obstacles related to course content. Additionally, the study revealed no statistically significant differences at the (0.05 ≥α) level concerning the average responses related to these obstacles based on gender, academic degree, or years of experience. Based on the study results, several recommendations were proffered.